2021
DOI: 10.48550/arxiv.2106.05175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Improved Bound for the Tree Conjecture in Network Creation Games

Abstract: We study Nash equilibria in the network creation game of Fabrikant et al. [10]. In this game a vertex can buy an edge to another vertex for a cost of α, and the objective of each vertex is to minimize the sum of the costs of the edges it purchases plus the sum of the distances to every other vertex in the resultant network. A long-standing conjecture states that if α ≥ n then every Nash equilibrium in the game is a spanning tree. We prove the conjecture holds for any α > 3n − 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The latter also proved that the PoA is constant for α ∈ O(n 1−ε ) for any fixed ε > 1 log n . For large α, it was shown by Bilò and Lenzner [24] that for α > 4n − 13 all Nash equilibria must be trees and this bound was recently improved by Dippel and Vetta [26] to α > 3n − 3. This implies a constant PoA for α > 3n − 3.…”
Section: Related Workmentioning
confidence: 99%
“…The latter also proved that the PoA is constant for α ∈ O(n 1−ε ) for any fixed ε > 1 log n . For large α, it was shown by Bilò and Lenzner [24] that for α > 4n − 13 all Nash equilibria must be trees and this bound was recently improved by Dippel and Vetta [26] to α > 3n − 3. This implies a constant PoA for α > 3n − 3.…”
Section: Related Workmentioning
confidence: 99%
“…While the original tree conjecture was disproven [1], it was reformulated to hold for α ≥ n. This is best possible, since non-tree networks in NE exist for α < n [33]. A recent line of research [1,37,33,2,3,5,20] proved the adapted conjecture to hold for α > 3n − 3, further refined the constant upper bounds on the PoA for tree networks, and showed that the PoA is constant if α > n(1 + ε), for any ε > 0. The currently best general bound on the PoA that holds for all α > 0 was established by Demaine et al [19].…”
Section: Related Workmentioning
confidence: 99%
“…A series of works have contributed to this threshold from 12n log n [12] to 273n [3], 65n [13], 17n [14], and to 4n − 13 [9]. Very recently a preprint by Dippel and Vetta [15] claimed an improved bound 3n − 3.…”
Section: Introductionmentioning
confidence: 99%